A contribution to the linguistic and editorial history of 'Lotte civili' by Edmondo De Amicis (Prassi Ecdotiche della Modernità Letteraria, 2021)
This study aims to retrace the linguistic and editorial history of Edmondo De Amicis’ Lotte civili, starting from the first edition by Nerbini (1899) until the definitive edition by Treves (1910). In particular, this study aims to sketch the physiognomy of each edition, deepening the changes that characterize the text.